Effects Of Sc-Co2 Process Parameters And Testa Removal On The Nutritional Quality Of Palm Kernel Cake - Bennama, Moftah Massaud (2014)
The main focus of the present study is to determine the effectiveness of the supercritical carbon dioxide (SC-CO2) extraction of residual oil from PKCM and production of defatted PKCM. This could be a quality source of the dietary fibre for human consumption either from PKCM SC-CO2 defatted palm kernels with testa (PKt), and without testa (PKw). Soxhlet extraction method was also applied to extract the oil from the PKt and PKCM. The SC-CO2 extraction of oil was performed under different pressures of 27.6, 34.5 and 41.4 MPa, temperatures of 40, 60 and 80 0C and extraction time of 30, 40 and 60 min at flow rate 2 ml/min. It was found that the oil extraction from PKt, PKw and PKCM was greatly influenced by particle size, pressure and temperature. The highest extracted oil yield was gained about 13%, 51% and 35% from PKCM, PKt and PKw, respectively; using SC-CO2 at particle size 0.05 mm, pressure 41.4 MPa, temperature 60oC for 40 min extraction time. The nutritional and anti-nutritional composition in the SC-CO2 treated palm kernel cake (i.e., SC-PKt, SC-PKw) and PKCM were determined. The results of the nutrient compositions in defatted PKCs show that SC-CO2 maintained the nutrient, and it does not affect the nutrient content in extracted sample by undergoing degradation. The highest protein content was determined in SC-PKt (18.7%) flowed by the PKw (15%) and then PKCM (13.5%). The total dietary fiber content was found to be 61.58%, 58.69 % and 60.71% in SC-PKt, SC-PKw and PKCM, respectively.